2015
DOI: 10.1214/15-aoas829
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet-domain regression and predictive inference in psychiatric neuroimaging

Abstract: An increasingly important goal of psychiatry is the use of brain imaging data to develop predictive models. Here we present two contributions to statistical methodology for this purpose. First, we propose and compare a set of wavelet-domain procedures for fitting generalized linear models with scalar responses and image predictors: sparse variants of principal component regression and of partial least squares, and the elastic net. Second, we consider assessing the contribution of image predictors over and abov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 85 publications
(149 reference statements)
2
45
0
Order By: Relevance
“…Following Reiss et al (2014) and Goldsmith, Huang, and Crainiceanu (2014), we simulate 500 images based on the first 332 weighted principal components from a subsample of ADHD-200 data (ADHD-200 Consortium 2012), where weights are randomly chosen from N(0,λ j ) withλ j , j = 1, . .…”
Section: Simulation Study-2d Image Predictormentioning
confidence: 99%
“…Following Reiss et al (2014) and Goldsmith, Huang, and Crainiceanu (2014), we simulate 500 images based on the first 332 weighted principal components from a subsample of ADHD-200 data (ADHD-200 Consortium 2012), where weights are randomly chosen from N(0,λ j ) withλ j , j = 1, . .…”
Section: Simulation Study-2d Image Predictormentioning
confidence: 99%
“…The fifth one (WNET) is to perform scalar-on-image regression in the wavelet domain by naive elastic net (Zhao et al 2014). Among these six approaches, the TV, Lasso, Lasso-Haar, and Matrix-Reg methods have been implemented by Matlab and the FPCR and WNET methods have been implemented in the R packages ‘refund’ and ‘refund.wave’ (see Reiss et al 2015), respectively. For the FPCR and WNET methods, we have used the default settings of both packages.…”
Section: Simulation Studiesmentioning
confidence: 99%
“…For example, the isotropic total variation penalty uses the Euclidean norm of the first differences of the parameter, rather than the sum of the absolute values of the first differences. There are a few papers on the use of two-dimensional or three-dimensional imaging predictors in FLM (Guillas and Lai 2010; Reiss and Ogden 2010; Zhou et al 2013; James, et al 2009; Goldsmith et al 2010; Gertheiss et al 2013; Wang et al 2014; Reiss et al 2015), but none of them consider the piecewisely smoothed function with jumps and edges and the total variation analysis. We also derive nonasymptotic error bounds on the risk for the estimated coefficient image under the total variation penalty.…”
Section: Introductionmentioning
confidence: 99%
“…Their success rate segregating both groups was close to 84%. In a paper from 2015, Reiss et al [26] showed their results for the ADHD challenge in which they analyzed resting state data (ReHo and ALFF images) of patients with ADHD using wavelet analysis.…”
Section: Wavelet Analysis Applied To Adhd Patients Using Mri Resting mentioning
confidence: 99%